An examination of the health and wellness of recruits and women in the U.S. fire service - Hollerbach, Brittany Sara (Kansas State University, 2019)
Background: Firefighting is a dangerous occupation, with high rates of line-of-duty injuries and fatalities as well as a high number of related psychological and physical health concerns. Poor health and low levels of firefighter (FF) fitness have significant economic costs for the individual, the fire department, and the public. Though FF fitness and injuries have been studied extensively among men in the fire service, research among recruits and women FFs is lacking. The purpose of this dissertation was to examine exercise training among recruits in the fire service as well as the perceptions, experiences, rates, types, and predictors of injuries among career women FFs. Methods: This dissertation is composed of three different studies. The first was a pilot 10-week randomized trial of a novel exercise intervention, The First Twenty High-Performance Training Program (TF20), with fire academy recruits. Second, we qualitatively examined injury perceptions among women FFs via focus groups and key informant interviews. Last, a cross-sectional study used snowball sampling to solicit participation from women career FFs; participants completed an online survey regarding occupational injuries, which were compared to those of men in the fire service, with a specific focus on behavioral health predictors of injury. Results: The pilot investigation was the first to examine TF20 among fire service recruits and found that recruits did not meet National Fire Protection Association (NFPA) physical fitness standards at baseline but did show improvements in body composition, muscular strength, agility, and aerobic capacity after the 10-week intervention. After examining fire recruits, interest in the lack of representation of women FFs arose, and the further investigations examined this “hidden population.” First, after examining women FFs’ perceptions and attitudes related to injury in the fire service, participants identified six key themes: the impact of working in a male-dominated field; harassment; the similar rates/types of injury among men FFs; inadequate training; ill-fitting protective gear; and functional techniques/endurance related to injury in the fire service. This qualitative analysis led to a quantitative examination of injury among women FFs. Several behavioral health predictors including exercise habits, being a former or current smoker, depression, and job dissatisfaction were statistically significant predictors of injury. Conclusions: Our data show that FFs, even new recruits, struggle with low levels of fitness. We also found that women experience similar rates and types of injury as their male counterparts, though their experiences with injury differ (e.g., they experience more chronic injuries, injuries related to discrimination and harassment, differing predictors of injury, and more missed days due to injury). Research among women FFs has shown that a lack of data negatively impacts recruitment and retention in the fire service. The combined information from these studies can help inform policy and training to address preliminary fitness training and injury prevention in the fire service to better protect all FFs.
Keywords: Firefighter; Occupation; Health; Wellness; Women; Recruit